HILAH Al-HUKMI Studi Perkembangan Teori Hukum Islam - Moh. Imron Rosyadi (Fakultas Syariah (Syari'ah Faculty ), 2016)
In the history of Islamic law development there were two boards mazhab: the first mazhab tended to use hadith to interpret Qur’anic verses and the second was based on logic. Later, the first was known as ahl al-hadith and the second was ahl al-ra’yi. Ahl al-hadith began to flourish in Madina and led by Imam Malik bin Anas while the latter spread in Kuffah and Bagdad in which Imam Abu Hanifah was the pioneer. Currently there are four products of syariah thought: fiqh books, fatwa of Islamic scholar, decision of syariah court, and acts or rules in Islamic states. Each of which has various characteristics for that it requires different attention. This article discusses hilah al-hukmi that is a product of Islamic scholar includes meaning, role, and Islamic scholars’ opinions about the relevancy of hilahto overcome syariah cases. In this study the writer uses qualitative analysis approach. He elaborates Islamic scholars’ opinions and then analyses them. He then concludes that hilah al-hukmi is still relevant to modern life and is not a deviation.